2014
DOI: 10.1111/iju.12613
|View full text |Cite
|
Sign up to set email alerts
|

Oral ethinylestradiol in castration‐resistant prostate cancer: A 10‐year experience

Abstract: Abbreviations & AcronymsObjectives: To describe our 10-year experience with the use of oral ethinylestradiol in the treatment of metastatic castration-resistant prostate cancer. Methods: From February 2000 to April 2010, 116 patients with a metastatic castrationresistant prostate cancer were prospectively submitted to oral ethinylestradiol monotherapy. Inclusion criteria were: diagnosis of castration-resistant prostate cancer after failure of at least two lines of androgen deprivation therapy and radiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 15 publications
0
23
1
Order By: Relevance
“…11,12 In short, these studies reported PSA response rates of EE ranging 57.1-73.3%, and a median time to progression ranging 7-15.1 months. The PSA response rate (percent of patients achieving a decline in PSA >50% from baseline) and median time to progression during EE therapy were 51.1% and 12.2 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 In short, these studies reported PSA response rates of EE ranging 57.1-73.3%, and a median time to progression ranging 7-15.1 months. The PSA response rate (percent of patients achieving a decline in PSA >50% from baseline) and median time to progression during EE therapy were 51.1% and 12.2 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Among estrogens, several authors investigated the effect of oral EE for CRPC treatment. [9][10][11] Among estrogens, several authors investigated the effect of oral EE for CRPC treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the usefulness of ethinyl-estradiol has been assessed in retrospective studies, and favorable results have been obtained, showing PSA PFS of 10 months in CRPC patients in Japan, and PFS of 15.1 months in metastatic CRPC in Western countries. 4,13 Administration of low-dose estramustine phosphate for CRPC showed a favorable response before docetaxel treatment (7.1-month median PFS, and 42-month overall survival in 31 patients with CPRC). 5 Also for dexamethasone, which has been used extensively for CRPC in Japan because of the benefit in treatment of CRPC, 14 the usefulness has been reconfirmed by a prospective study in Western countries comparing dexamethasone and prednisone for treatment of CRPC, in which PFS periods were 9.7 and 5.1 months, respectively.…”
Section: Vintage Hormonal Therapymentioning
confidence: 99%
“…In addition, estrogen‐related drugs, such as estramustine phosphate and ethinyl‐estradiol, have also been used for post‐recurrence of alternative antiandrogen therapy. In particular, the usefulness of ethinyl‐estradiol has been assessed in retrospective studies, and favorable results have been obtained, showing PSA PFS of 10 months in CRPC patients in Japan, and PFS of 15.1 months in metastatic CRPC in Western countries . Administration of low‐dose estramustine phosphate for CRPC showed a favorable response before docetaxel treatment (7.1‐month median PFS, and 42‐month overall survival in 31 patients with CPRC) .…”
Section: Vintage Hormonal Therapymentioning
confidence: 99%